An Analysis of Forming the Corporate Identity of a Merger Organisation in Nokia Siemens Networks - Cham, Jeanie (2009)
The aim of this dissertation is to study how Nokia Siemens Networks, a newly merged organisation, developed and communicated its corporate identity. This research starts with a detailed literature review that highlights the issues regarding corporate identity crucial for well-being of employees and achieving organisational success.